2016
DOI: 10.3390/ijms17081336
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Maternal High-Fat Intake Dynamically Programmed mRNA m6A Modifications in Adipose and Skeletal Muscle Tissues in Offspring

Abstract: Epigenetic mechanisms have an important role in the pre- and peri-conceptional programming by maternal nutrition. Yet, whether or not RNA m6A methylation—an old epigenetic marker receiving increased attention recently—is involved remains an unknown question. In this study, mouse high-fat feeding prior to conception was shown to induce overweight and glucose intolerant dams, which then continued to be exposed to a high-fat diet during gestation and lactation. The dams on a standard diet throughout the whole exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
(58 reference statements)
0
28
0
Order By: Relevance
“…These observations highlight that m 6 A RNA methylation plays an important role in energy and lipid metabolism. Interestingly, mouse maternal high‐fat diet affects mRNA m 6 A modifications and its related genes in the offspring (Li et al, ), suggesting that dietary factors affect the mRNA m 6 A levels. Here we observed that dietary curcumin increased the content of m 6 A and affected its related gene expressions in the liver of piglets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations highlight that m 6 A RNA methylation plays an important role in energy and lipid metabolism. Interestingly, mouse maternal high‐fat diet affects mRNA m 6 A modifications and its related genes in the offspring (Li et al, ), suggesting that dietary factors affect the mRNA m 6 A levels. Here we observed that dietary curcumin increased the content of m 6 A and affected its related gene expressions in the liver of piglets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, m 6 A RNA methylation affects many biological processes, including cellular differentiation, body mass, and metabolism, indicating its role in obesity, cancer, and other human diseases (Lin, Choe, Du, Triboulet, & Gregory, ; Wang, Li, et al, ; Zheng et al, ). Recent studies have shown that dietary factors affect the RNA m 6 A levels (Li et al, ). However, the effect of curcumin on m 6 A RNA methylation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, upregulation of FTO gene expression was closely associated with skeletal muscle mass increase in overweight individuals ( Doaei et al, 2019 ). Moreover, maternal high-fat intake could even disturb the m 6 A modification and FTO gene expression in skeletal muscle of its offspring ( Li et al, 2016 ). Wu et al (2017) have confirmed that activation of AMPK decreases the lipid accumulation in skeletal muscle cells through inversely regulating FTO expression and FTO-mediated demethylation.…”
Section: Rna M 6 a Methylation In Musculoskeletal mentioning
confidence: 99%
“…Li et al . (2016) indicated that a maternal high‐fat diet downregulated FTO and upregulated the METTL3 levels, resulting in increased m 6 A methylation in the visceral fat of three‐week‐old mice . However, FTO expression in the hypothalamus was significantly increased in rats fed a high‐fat diet, resulting in obesity .…”
Section: M6a Nutrition and Metabolismmentioning
confidence: 99%